The Sestamibi Paradox: Improving Intraoperative Localization of Parathyroid Adenomas. Issue 8 (August 2017) - Buicko, Jessica L.; Kichler, Kandace M.; Amundson, Julia R.; Scurci, Stephanie; Kozol, Roberta
Accurate localization of parathyroid adenomas allows for minimally invasive parathyroidectomy. This results in a shorter length of stay and increased patient satisfaction. Preoperative Technetium ( 99m Tc) sestamibi scans accurately localize parathyroid adenomas in 70 to 85 per cent of cases. If a patient has a negative scan, it is logical to believe that with a preoperative sestamibi injection, the gamma probe may fail to help find an adenoma. We hypothesized that the gamma probe would not be useful intraoperatively for patients with primary hyperparathyroidism (PHPTH) and a negative sestamibi scan. We retrospectively reviewed the cases of parathyroidectomy at our institution from 2010 to 2016. We selected patients with PHPTH and negative sestamibi scan. In all cases, an attempt was made to find adenomas intraoperatively with the gamma probe. A frozen section was obtained as well as intraoperative parathyroid hormone levels to confirm removal of hyperfunctioning parathyroid tissue. There were 132 parathyroidectomies of which 22 had PHPTH and a negative sestamibi scan. One case was excluded because of insufficient documentation of the intraoperative use of the gamma probe. In 19 of the 21 patients analyzed, the gamma probe successfully identified the adenoma in the operating room (sensitivity, 90.5%). In two patients, the gamma probe did not aid in localization. There were no false positives. In all cases, the parathyroid resected was confirmed by frozen section. The intraoperative parathyroid hormone levels dropped >50 per cent in all but three cases, two of which corresponded to those cases where the gamma probe did not help. Even in patients with negative sestamibi scans, intraoperative use of the gamma probe after preoperative sestamibi injection is effective in localizing parathyroid adenomas.